Studi Provenance Batupasir Formasi Peneta Desa Slango, Kabupaten Sarolangun, Jambi - Lokon, Beskian; Edy Sutriyono (Jurnal Universal Technic, 2024)
This research was conducted in Slango village, Sarolangun Regency, Jambi. This research focuses on analyzing the source of rock origin, namely sandstone found in the Peneta Formation. Sandstone in the study area is quite widely distributed with varied characteristics, so determining the original rock is easy to do. This research was carried out to identify the origin of the rock through petrographic analysis of the sandstone so that the history of the formation of the Peneta Formation itself can be reconstructed. After provenance analysis, the Peneta Formation sandstone comes from the Recycle Orogen, precisely in the Subduction Complex Sources subzone. Apart from that, the Peneta sandstone also shows the origin of the Magmatic Arc. Thus, it is interpreted that the Peneta Formation sandstone has undergone several uplift processes due to tectonic activity and has experienced increased maturity or stability from the Continental Block Provenances. Apart from that, it is also influenced by the weathering process of granite heights or other volcanic materials, whether volcanic or plutonic. Key words: Sandstone, Slango Village, Peneta Formation, Petrography, Provenance